Detergent waste phytoremediation using Mexican-Sword plant (Echinodorus paleafolius) in household application / Rifkah Sulistyawati, Marwah Amalia and Sharfina Mutia Syarifah - Sulistyawati, Rifkah; Amalia, Marwah; Syarifah, Sharfina Mutia (2022)
Detergent waste is a leftover washing-process water that is difficult to decompose, which can pollute water and harm aquatic habitats. One way to lessen the toxicity of detergent waste is by using phytoremediation plants. The purpose of this study is to evaluate the possibility for Mexican-Sword plants to be used in domestic applications for phytoremediation. In this application, a reactor with a single plant type and a filter layer made of activated charcoal and zeolite sand is used. The wastewater is diluted and stored in the reactor for filtration, then the wastewater will be pumped into the environment through a water faucet. The reactor is designed to hold about 15 liters of water in a single hold which will take up to four days for the phytoremediation process, before it is discharged through the faucet directly to the drainage. It can be applied in households to produce greener environmental waste. The results of the research on Mexican-Sword plants have the potential for phytoremediation, which is indicated by the clear form of detergent wastewater and the growth of Mexican-Sword plants as the waste is absorbed by them. However, further research is still needed to increase the capacity as well as to reach the target as zero waste.